2015
DOI: 10.3390/ijms161226136
|View full text |Cite
|
Sign up to set email alerts
|

The Historical Development of Immunoendocrine Concepts of Psychiatric Disorders and Their Therapy

Abstract: Relationships between the central nervous, immune and endocrine systems are a focus of psychiatric research, particularly in depression and schizophrenia. The field has long antecedents. Observed phenomena attributable to these relationships date back to the Neolithic era. Immunoendocrine theories in the broadest sense are recorded in antiquity. In the 19th century, Kraepelin and Wagner-Jauregg reported pioneering clinical observations in psychiatric patients. Von Basedow, Addison and Cushing described psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 127 publications
(139 reference statements)
0
5
0
2
Order By: Relevance
“…Psychosis arising either with the occurrence or disappearance of acute fever has been described by many scientists from Hippocrates around 400 BC to Kraepelin around 1900. In the 1930s it was first hypothesized by Hermann Lehmann-Facius that schizophrenia was the product of an autoimmune reaction with antibodies attacking brain tissue ( 1 ). In the 1950s and 1960s it was noticed that celiac disease seemed to occur more often within those suffering from schizophrenia than in the general population ( 2 ), and conversely, that schizophrenia occurred less frequently within patients with rheumatoid arthritis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychosis arising either with the occurrence or disappearance of acute fever has been described by many scientists from Hippocrates around 400 BC to Kraepelin around 1900. In the 1930s it was first hypothesized by Hermann Lehmann-Facius that schizophrenia was the product of an autoimmune reaction with antibodies attacking brain tissue ( 1 ). In the 1950s and 1960s it was noticed that celiac disease seemed to occur more often within those suffering from schizophrenia than in the general population ( 2 ), and conversely, that schizophrenia occurred less frequently within patients with rheumatoid arthritis ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of IL-6 in AN patients have been inconsistent, and recent meta-analyses have concluded that levels of pro-in ammatory cytokines tumor necrosis factor -α and interleukin-6 were elevated in AN patients compared with healthy subjects [10,25],While this may seem contradictory to decreased CRP levels, Il-6 production can be thought of as a state-dependent distribution mechanism: the more fat you store, the more IL-6 is produced, and the increased IL-6 stimulates fat breakdown, leading to weight loss [48]. Anorexia patients have very low levels of neuropeptide Y and leptin, and excessive levels of TNF β, which inhibit the hypothalamus feeding center leading to anorexia, and further lead to changes in CRP [69].Secondly, Cytokines are thought to be involved in the pathophysiology of many mental disorders, and existing studies on depression, anxiety and obsessive-compulsive disorders have shown elevated CRP levels [49][50][51][52]. Comorbidity is common in patients with AN, such as depression, anxiety and obsessive-compulsive symptoms [53][54][55], In theory CRP levels should be elevated in AN patient.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines regulate hypothalamic neurons [14], Induced changes in catecholamine system and opioid system [15], which are involved in regulating feeding behavior and appetite. By integrating signals received from the periphery about nutritional status, saturation and food intake, the hypothalamus regulates food intake and energy expenditure [69].Some studies also con rmed that AN seems to be associated with increased pro-in ammatory cytokines such as plasma/serum levels of tumor necrosis factor-alpha (TNF-α), interleukin (IL)-1beta (IL-1β) and IL-6 [10][11][12][13],…”
Section: Introductionmentioning
confidence: 99%
“…Po inokulacji pierwotniaka zarodźca malarii (Plasmodium vivax) u chorych tych następowały rzuty gorączki, ale w późniejszym okresie dochodziło do istotnej poprawy stanu psychicznego. Za wprowadzenie tej metody, którą można uznać za początek immunoterapii, Wagner--Jauregg został w 1927 roku uhonorowany Nagrodą Nobla [7]. Co ciekawe, obserwacje dotyczące poprawy zaburzeń psychicznych po przechorowaniu malarii poczynił ponad wiek wcześniej polski lekarz Ludwik Perzyna (1742-1800), którego imieniem jest nazwany Szpital Wojewódzki w Kaliszu, w swym dziele Lekarz dla włościan [8].…”
Section: Kiłaunclassified